Increasing the Space–Time Resolution of Mapped Sea Surface Height From Altimetry. Issue 6 (11th June 2020) - Archer, Matthew R.; Li, Zhijin; Fu, Lee‐Lueng
Abstract: We present a mapping methodology to improve the resolution of gridded sea surface height (SSH) from multisatellite along‐track measurements, and apply it in the California Current system. This is motivated by the upcoming Surface Water and Ocean Topography (SWOT) satellite mission, which will collect novel high‐resolution wide‐swath SSH measurements. The calibration/validation of SWOT will be in the California Current and requires independent observations of SSH spatial variability. Our objective was to discover how far we could push the space–time resolution of SSH maps based on the existing altimetry constellation. Currently, the best SSH maps for the region are from AVISO's global product based on optimal interpolation (OI). Our methodology is based on 2‐D variational analysis (2DVAR), and we address some limitations of the AVISO OI global parameterization that restrict the resolution. Key improvements are (1) use of a background field incorporating mesoscale information, as opposed to a long‐term mean field; (2) optimized regional parameters; and (3) a representation error term in the observational error covariance matrix to account for the spread of measurements in time. Using a suite of independent remote and in situ observations, we show the 2DVAR method can produce higher‐resolution SSH maps in the California Current region that successfully capture smaller‐scale ocean features than AVISO, at the expense of an increase in noise. Plain Language Summary: Satellite altimeters measure sea surface height (SSH) along one‐dimensional tracks across the ocean. Multiple tracks taken over a time window can be mapped onto a regularly spaced longitude‐latitude‐time grid to provide information of ocean variability that allows for a range of analyses. Here, we revisit the mapping process, motivated by the upcoming Surface Water and Ocean Topography (SWOT) satellite mission that will provide unprecedented high‐resolution measurements of SSH. SWOT will be calibrated/validated in the California Current, but currently, the best maps for comparison are from a global product not tailored to the region. While along‐track measurements resolve the SSH signal down to ~65 km, these maps only resolve scales > 200 km. Our goal was to increase map resolution by retaining more of the along‐track SSH signal. We developed a mapping methodology based on variational analysis. The new maps have higher variability at smaller scales, at the expense of an increase in noise. We show these maps compare better to independent data from in situ observing platforms, coastal radar, and satellite imagery of temperature and chlorophyll‐a. The ability to resolve shorter space–time scales of variability can have important implications for the study of ocean dynamics from altimetry. Key Points: We develop a mapping methodology to grid multisatellite along‐track measurements of sea surface height in the California Current system This variational method prescribes regionally optimized parameters, an improved background field, and an observational representation error The new maps retain finer‐scale signals from the along‐track observations and compare well with a suite of independent observations